Crystal growth, structure and magnetic properties of Ca10Cr7O28. (28th April 2017) - Balz, Christian; Lake, Bella; Reehuis, Manfred; Nazmul Islam, A T M; Prokhnenko, Oleksandr; Singh, Yogesh; Pattison, Philip; Tóth, Sándor
Abstract: A detailed diffraction study of Ca10 Cr7 O28 is presented which adds significant new insights into the structural and magnetic properties of this compound. A new crystal structure type was used where the a and b axes are doubled compared to previous models providing a more plausible structure where all crystallographic sites are fully occupied. The presence of two different valences of chromium was verified and the locations of the magnetic Cr 5+ and non-magnetic Cr 6+ ions were identified. The Cr 5+ ions have spin- 1 2 and form distorted kagome bilayers which are stacked in an ABC arrangement along the c axis. These results lay the foundation for understanding of the quantum spin liquid behavior in Ca10 Cr7 O28 which has recently been reported in Balz et al (2016 Nat. Phys .12 942).